2021
DOI: 10.1002/alz.12251
|View full text |Cite
|
Sign up to set email alerts
|

The risk of dementia after coronary artery bypass grafting in relation to age and sex

Abstract: Introduction:We examined the long-term risk of dementia after coronary artery bypass grafting (CABG) in relation to age and sex.Methods: All CABG patients in Sweden 1992Sweden -2015, and matched controls (n = 222,396) were included in a population-based study. Adjusted hazard ratios (aHR) for all-cause dementia, vascular dementia, and Alzheimer's disease were calculated.Results: There was no difference in the risk for all-cause dementia between CABG patients and control subjects (aHR 0.98 [95% confidence inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 27 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have shown that younger, but not older, patients undergoing CABG have an increased risk of dementia in comparison with an aged-and sex-matched control population. 5 The present study shows a significant correlation between the ongoing use of statins and a reduced risk of dementia (adjusted hazard ratio, 0.75), which could motivate patients and doctors to continue with statins, even for a long time after surgery. The main reason for discontinuing the medication with statins may be the relatively high incidence of side effects, such as statin-associated muscle symptoms or central nervous system complaints.…”
mentioning
confidence: 55%
“…Previous studies have shown that younger, but not older, patients undergoing CABG have an increased risk of dementia in comparison with an aged-and sex-matched control population. 5 The present study shows a significant correlation between the ongoing use of statins and a reduced risk of dementia (adjusted hazard ratio, 0.75), which could motivate patients and doctors to continue with statins, even for a long time after surgery. The main reason for discontinuing the medication with statins may be the relatively high incidence of side effects, such as statin-associated muscle symptoms or central nervous system complaints.…”
mentioning
confidence: 55%
“…Patients who had undergone CABG (n = 111 335) in the SWEDEHEART registry compared with matched controls from the general population (n = 222 396) had similar rates of dementia, especially in older patients. Further, among patients who had undergone CABG, vascular risk factors, such as hypertension and diabetes, remained important factors associated with dementia . In contrast, other studies have found support for an association between CABG and risk of dementia, although importantly, in these observational studies, there was the potential for residual confounding.…”
mentioning
confidence: 83%
“…CABG patients younger than 75 years were at an increased risk and CABG patients older than 75 years were at a decreased risk for developing allcause dementia compared with age-matched control participants. 79 Another study showed a greater prevalence of acute postoperative NCD in younger patients, although most returned toward baseline by the 1-month followup. 80 Younger patients were also shown to have higher levels of perioperative inflammatory markers.…”
Section: Long-term Outcomes and Quality Of Lifementioning
confidence: 97%